Hubungan Sikap Ibu Hamil Terkait Perilaku Hidup Bersih dan Sehat dengan Kejadian Bakteriuria Asimptomatik - Zahra Sabrina Wahyu; Nadyah Haruna; Najamuddin Palancoi Palancoi; Henny Fauziah (Rumah Sakit Ibnu Sina, Makassar, 2025)
Asymptomatic bacteriuria (ASB) during pregnancy may progress to urinary tract infection (UTI) and complications if undetected. Attitudes toward clean and healthy living behavior (PHBS) may be associated with ASB risk through genital hygiene, voiding habits, and hydration. To examine the association between PHBS attitudes and ASB among pregnant women at Jongaya Primary Health Center, Makassar. An analytical cross-sectional study (December 2023–January 2024) involving 56 pregnant women (accidental sampling). The independent variable was PHBS attitude (poor/moderate/good) measured using a PHBS attitude questionnaire. The dependent variable was operational ASB, determined by urine testing (dipstick leukocyte esterase/nitrite and/or urine sediment analysis) among participants without UTI symptoms based on a symptom-screening checklist interview. Chi-Square was used for association testing; due to small cell counts, a sensitivity analysis using category collapsing and exact testing was performed, with effect sizes (PR/OR) and 95% CIs reported. Poor PHBS attitude was found in 27 (48.2%), moderate in 11 (19.6%), and good in 18 (32.1%). Operational ASB was identified in 44 participants (78.6%). Chi-Square indicated a significant association (p=0.01). After collapsing categories (poor vs moderate/good), poor attitude showed higher ASB prevalence (PR=1.55; 95% CI: 1.16–2.08) and higher odds (OR=15.89; 95% CI: 1.88–134.18) with exact p=0.002. PHBS attitude was statistically associated with operational ASB in this setting. Causal inference cannot be made due to the cross-sectional design and potential confounding.